Pengaruh Kreativitas Dalam Iklan, Reputasi Bintang Iklan Dan Waktu Penayangan Iklan Terhadap Efektivitas Iklan Serta Dampaknya Terhadap Minat Pembelian Konsumen - Wibowo, Bambang Setia (208-7721)
This study examined the influence of creative advertising, endorser, and advertising time to advertising effectiveness and its impact to consumer purchase intention. 100 university students who have ever seen shampoo advertisements on television participated in this reseach. There are several findings in this study. First, creativity in advertising has positive effect to advertising effectiveness. Second, endorser has positive influence to the advertising effectiveness. Third, advertising time has positive effect to advertising effectiveness. Fourth, advertising effectiveness hasÂ  positive effect on consumer purchase intention. Fifth, advertising effectiveness perfectlyÂ  mediate the effect of creativity in advertising, endorser and advertising time to the consumer purchase intention.